In vitro antioxidant and antibacterial evaluations of propolis from South Kalimantan, Indonesia. Issue 1 (1st June 2022) - Nisa, K; Damayanti, E; Sunardi,; Byasih, N; Norhasanah,
Abstract: Propolis, a complex substance of resinous, is produced by honeybees. Propolis contains a number of flavonoid compounds endowed with antimicrobial and antioxidant capabilities. The main chemical constituents and physicochemical properties of propolis are depended on many factors including geographic origin. This study was undertaken to evaluate antibacterial, antibiofilm, and antioxidant activities of propolis collected from Kalimantan, Indonesia. The phytochemical properties of propolis were identified by total phenolic contents, total flavonoid contents, and FTIR analysis. Propolis was extracted using 96% ethanol, 70% ethanol, and n-hexane solvents. Moreover, the bioactivity capacity of propolis extracts were observed through antioxidant and antibacterial activities. The results showed that propolis extracts exhibited varying degrees of phenolic content, flavonoid contents, antibacterial, and antiradical scavenging properties. The highest value of total flavonoid content was obtained on 96% ethanol propolis extract as well as its remarkable antibacterial and antiradical scavenging activities.